1997
DOI: 10.1006/viro.1997.8833
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interactions between Human Integrin αvβ3and Chimeric Hepatitis B Virus Core Particles Bearing the Receptor-Binding Epitope of Foot-and-Mouth Disease Virus

Abstract: Purified integrin alpha v beta 3 was used in solid-phase binding studies with chimeric hepatitis B cores which carry the RGD-containing loop of VP1 protein of the foot-and-mouth disease virus (FMDV). High levels of specific binding between the integrin and the particles were detected by enzyme-linked immunosorbent assays. The binding was Mn2+ cation dependent and could be competed with fibronectin, vitronectin, and the peptide GRGDSPK. Particles in which the RGD motif had been mutated to RGE failed to bind, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In some of these instances, this tripeptide has been shown to play an important role in the process of viral infection by mediating primary or secondary interactions between the virion and cell surface-localized integrins. Furthermore, recent studies showed that genetic incorporation of the RGD-containing sequences into chimeric hepatitis B cores (11,36), poliovirus particles (30), bacteriophage fd (19,20), and human Ad virions (44) allows specific interaction of these viral particles with cellular integrins, thereby resulting in binding of aforementioned structures to cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these instances, this tripeptide has been shown to play an important role in the process of viral infection by mediating primary or secondary interactions between the virion and cell surface-localized integrins. Furthermore, recent studies showed that genetic incorporation of the RGD-containing sequences into chimeric hepatitis B cores (11,36), poliovirus particles (30), bacteriophage fd (19,20), and human Ad virions (44) allows specific interaction of these viral particles with cellular integrins, thereby resulting in binding of aforementioned structures to cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA. Solid-phase binding assay was performed by a method previously described by Sharma et al (36). Briefly, purified fiber proteins or Ad virions were diluted in 50 mM carbonate-bicarbonate buffer, pH 9.6, to a concentration of 10 g of protein per ml, and 100-l aliquots were added to the wells of a 96-well Nunc-Maxisorp enzyme-linked immunosorbent assay (ELISA) plate.…”
Section: Cells and Tissuesmentioning
confidence: 99%
“…Purification of Integrin ␣ 5 ␤ 1 -Integrin ␣ 5 ␤ 1 was purified from human placenta as described previously (21), with some modifications. Briefly, a placenta was homogenized in 200 ml ice-cold lysis buffer (50 mM Tris-HCl, pH 7.4, 1 mM MgCl 2 , 1 mM MnCl 2 , 1 mM CaCl 2 , 150 mM NaCl, 1% Triton X-100) containing sodium vanadate (1 mM), leupeptin (10 g ml Ϫ1 ), aprotinin (10 g ml Ϫ1 ), and phenylmethylsulfonyl fluoride (1 mM).…”
Section: Methodsmentioning
confidence: 99%
“…The second mutant, E-390 (D3E), was constructed for two reasons: first, because it represented a conservative amino acid change, and second, because other flaviviruses such as West Nile virus (WNV) (72) and KUN (15) possess an RGE as opposed to an RGD motif in this region of the protein. Substitution of a Glu residue at the third position of an RGD motif has been shown to abolish RGD-dependent integrin binding by a range of viruses, including FMDV (44), chimeric hepatitis B virus (64), and echovirus type 9 (76). The last mutant, E-390 (D3Y), was constructed because it represented the substitution of a large hydrophobic amino acid residue into a strongly hydrophilic region of the protein.…”
Section: Phenotypes Of E-277 (Hinge) Mutant Viruses In Vitromentioning
confidence: 99%